An externally cross-linked heat-resistant and salt-resistant thickener

Through the chemical crosslinking of silver nitrate/cerium nitrate-persulfate composite catalytic system with PAA or PMAA, the problems of poor salt resistance and high-valent ion pollution of traditional thickeners are solved, and the high viscosity and temperature resistance are improved. Suitable for continuous fracturing operations and flexibly adjust the viscosity-launched time of thickener.

CN116376533BActive Publication Date: 2025-01-03PUYANG GREEN SINGULARITY NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310362161.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-03
Publication Date
2025-01-03
Estimated Expiration
2043-04-03

AI Technical Summary

Technical Problem

Traditional thickeners are poor in salt resistance when used in high mineralization water. The pH value of the aqueous solution needs to be adjusted to control the crosslinking reaction, resulting in waste of resources and environmental pollution. At the same time, high-priced ionic crosslinking agents have toxicity and pollution risks, which are difficult to meet the continuous Requirements for fracturing operations.

Method used

The PAM and PAA molecular chains were chemically crosslinked by silver nitrate/cerium nitrate-persulfate composite catalytic system. By PAA or PMAA as crosslinking agent, it used its proton exchange reaction with the PAM molecular chain to generate covalent bonds to form high Viscosity crosslinked gel avoids pH adjustment and high-valent ions use.

Benefits of technology

It improves the temperature and salt resistance of the thickener, simplifies the process flow, reduces environmental pollution, meets the high viscosity requirements of continuous fracturing operations, and flexibly adjusts the viscosity time by adjusting the catalyst amount.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an external cross-linking heat-resistant and salt-resistant thickener. The thickener comprises the following components by weight: 40-50 parts of white oil, 50-60 parts of anionic polyacrylamide (PAM) powder, 2-5 parts of thixotropic additive, 0.5-3 parts of cross-linking agent, and catalyst I and catalyst II are both 1%-5% of the cross-linking agent mass; the thickener of the invention catalyzes the decarboxylation and coupling reaction of polyacrylic acid structural units through a silver ion-persulfate composite system, so that chemical cross-linking occurs between poly(meth)acrylic acid or PAM molecules, and obtains a high-viscosity, heat-resistant and salt-resistant thickener gel liquid, which is suitable for continuous construction operations such as fracturing and seam-making of oil reservoirs in deep well oil and gas fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention specifically relates to an external cross-linking thickener and also relates to a preparation method of the thickener, belonging to the technical field of fracturing fluid for oil field reservoir reconstruction. Background Art

[0002] Hydraulic fracturing technology is a common technology for increasing the production of low-permeability oil and gas fields. The thickener is dissolved in water to obtain a thickener aqueous solution with a suitable viscosity. The viscosity of the thickener aqueous solution determines its sand-carrying capacity, pressurization effect and material cost. Generally speaking, the viscosity of the thickener aqueous solution is related to the structural unit composition and molecular weight of the polymer (polyacrylamide, PAM). Generally, the larger the molecular weight of the anionic PAM, the more physical entanglement points are formed between the PAM molecular chains, and the greater the apparent viscosity of the PAM aqueous solution; when a small amount (2-5%) of rigid groups such as sodium styrene sulfonate is introduced into the PAM molecular chain, the stronger the ability of the PAM aqueous solution to resist the collapse of the local structure of the PAM molecular chain caused by divalent positive ions (such as calcium and magnesium ions), that is, the better the salt resistance; when hydrophilic groups (such as vinyl pyrrolidone, acryloylmorpholine, etc.) are introduced into the PAM molecular structure, the faster the water dissolution rate of PAM is, which can effectively improve the production efficiency of the construction process.

[0003] During fracturing construction, a large amount of water is required to prepare the thickener aqueous solution. If seawater, flowback water and other resources can be used to prepare the thickener aqueous solution on site, a large amount of fresh water resources can be saved. However, the mineralization of flowback water, seawater, etc. is relatively high (containing a large amount of calcium, magnesium, potassium, and sodium ions). The calcium and magnesium ions coordinate with the carboxyl groups on the anionic PAM molecular chains, causing the local chain segments of the PAM hydration structure to collapse and precipitate, reducing the apparent viscosity of the thickener aqueous solution, which is manifested as poor salt resistance of the thickener. In order to improve the salt resistance of the thickener, a rigid sodium styrene sulfonate structure is often introduced into the PAM molecular chain to shield the complexation of multivalent ions such as calcium and magnesium ions with the carboxylic acid group, and prevent the viscosity from decreasing due to the local collapse of the PAM molecular chain. However, the polymerization reaction rate constants between sodium styrene sulfonate and acrylamide and acrylic acid monomers are quite different, which complicates the polymerization reaction process and makes the control of the polymerization reaction process more demanding and cumbersome. In order to solve the process and control problems of copolymerization of multiple monomers, in addition to introducing rigid sodium styrene sulfonate into PAM molecules to improve the salt resistance of the thickener, high-valent zirconium (IV), chromium (III), and aluminum (III) ions can also be added to react with the acid carboxyl groups on the PAM molecular chain to form physical crosslinks to increase the viscosity of the thickener aqueous solution. The physical crosslinking points formed by this complexation have a certain strength and can eliminate the local collapse damage caused by calcium and magnesium ions on the PAM molecular chain; at the same time, they can also resist the effect of a certain ambient temperature on the viscosity reduction, that is, when the ambient temperature changes, the crosslinking effect of high-valent positive ions such as zirconium, chromium, and aluminum on the PAM molecular chain is strong enough, and the physical crosslinking structure will not be destroyed by molecular thermal motion, showing good temperature resistance. But in fact, the reaction rate of high-valent positive ions such as zirconium, chromium, and aluminum in coordination with the carboxyl groups on the PAM molecular chain is greatly affected by the pH value of the aqueous solution. For example, when the pH values ​​of zirconium ions are 2.42, 4.02, 7.70 and 11.72, the viscosity of the cross-linked PAM aqueous solution is 1.74Pa·s, 4.60Pa·s, 8.59Pa·s and 0.272Pa·s respectively (Zhao Fulin, Li Liuren. Single-liquid zirconium gel plugging agent, Journal of Petroleum University, 1996, 20, 43-46.). This shows that the pH value of the aqueous solution has an appropriate range, and too high or too low pH values ​​are not conducive to the cross-linking of PAM molecular chains. However, to adjust the pH value of the thickener aqueous solution, a large amount of acid or alkali needs to be added, which not only causes waste of materials but also causes pollution of water resources. At the same time, the high-priced zirconium, chromium and aluminum ions themselves have certain toxicity. When added to the thickener as a cross-linking agent, it will also cause environmental pollution or damage. Summary of the invention

[0004] In order to solve the above problems, the present invention proposes an external cross-linking type heat-resistant and salt-resistant thickener, which solves the problem that the traditional high-valent ion cross-linking agent needs to adjust the pH value of the aqueous solution, and the toxic side effects of high-valent ions polluting the environment. It also improves the viscosity of the thickener solution, solves the defect of poor heat and salt resistance of traditional thickeners, and can meet the requirements of continuous fracturing operations.

[0005] To achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:

[0006] Externally cross-linked heat-resistant and salt-resistant thickener, the thickener comprises, by weight:

[0007]

[0008] Wherein, the basic thickener comprises, by weight:

[0009] 50-60 parts of anionic polyacrylamide (PAM) powder,

[0010] 40-50 parts of white oil,

[0011] 2-5 parts of thixotropic additive,

[0012] The catalyst I is silver nitrate;

[0013] The catalyst II is at least one of ammonium persulfate, potassium persulfate, sodium persulfate, potassium hydrogen persulfate, ammonium cerium nitrate, cerium nitrate, and cerium nitrate hexahydrate;

[0014] Furthermore, the thickener is prepared according to the following method:

[0015] (1) white oil and thixotropic additive are uniformly mixed, anionic polyacrylamide (PAM) powder is dispersed in the white oil under stirring at room temperature to 90° C., and then cooled to room temperature to obtain a basic thickener;

[0016] (2) Add a crosslinking agent under stirring conditions at room temperature and stir until the mixture is uniform;

[0017] (3) In another container, add deionized water and prepare a 1%-10% (mass percentage) solution of catalyst I under light-proof conditions;

[0018] (4) In another container, add deionized water to prepare a 1%-10% (mass percentage) solution of Catalyst II;

[0019] (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

[0020] Preferably, the anionic polyacrylamide (PAM) is selected from one or more of polymers (I) to (V),

[0021]

[0022] Among them, the average diameter of anionic polyacrylamide (PAM) is 80-120 μm, and the molecular weight is 1.5×10 7 g / mol-2.8×10 7 g / mol, a, o, m, n, p are all positive integers ≥ 1, and m:n = 1.5 to 3:1.

[0023] Preferably, the cross-linking agent is at least one of acrylic acid (AA), methacrylic acid (MAA), polyacrylic acid (PAA), polymethacrylic acid (PMAA), a copolymer of acrylic acid and methacrylic acid (PAA-co-PMAA), polyethylene glycol-b-polyacrylic acid (PEO-b-PAA), polyethylene glycol-b-polymethacrylic acid (PEO-b-PMAA), polyethylene glycol-b-polyacrylic acid-b-polymethacrylic acid (PEO-b-PAA-b-PMAA), and polyethylene glycol-b-acrylic acid copolymerized with methacrylic acid (PEO-b-PAA-co-PMAA).

[0024] Furthermore, the molecular weight of the P(M)AA block in the PAA, PMAA or PEO-bP(M)AA, PEO-b-PAA-co-PMAA block polymer is in the range of 500-500000 g / mol.

[0025] Preferably, the thixotropic agent is organic bentonite.

[0026] Preferably, the kinematic viscosity of the white oil is 2-18 mm 2 / s(40℃).

[0027] Preferably, the white oil is at least one of No. 3 white oil, No. 5 white oil, No. 7 white oil, No. 10 white oil, No. 15 white oil, and No. 32 white oil.

[0028] Compared with the prior art, the present invention has at least the following beneficial effects:

[0029] The thickener of the present invention chemically cross-links PAM and PAA molecular chains through a silver nitrate / cerium nitrate-persulfate composite catalytic system, and the obtained cross-linked thickener hydrogel has high viscosity and good temperature and salt resistance, and the cross-linking reaction rate (i.e., viscosity initiation time) can be flexibly adjusted, thereby solving the problem that traditional high-valent ion cross-linking agents need to adjust the aqueous solution to be acidic, overcoming the defect of poor temperature and salt resistance of traditional thickeners, and being able to meet the needs of continuous preparation of fracturing operations.

[0030] (1) Poly(meth)acrylic acid (PAA or PMAA) is a commonly used scale inhibitor in the water treatment industry, which is non-polluting to water and the environment. PAA or PMAA is weakly acidic when dissolved in water, and can complex with some calcium and magnesium ions, reducing the chance of calcium and magnesium ions reacting with PAM. Therefore, when PAA or PMAA is used as a cross-linking agent for thickeners, there is no special requirement for the water quality of the thickener (highly mineralized drilling return water or seawater can be used nearby as the solvent for the thickener), which can save a lot of fresh water resources.

[0031] (2) The mechanism of PAA or PMAA as a crosslinking agent to crosslink the PAM molecular chains is shown in VI.

[0032] The hydrogen protons of the carboxyl groups in the (meth)acrylic acid monomer, PAA, and PMAA structures can exchange protons with the sodium acrylate in PAM, so that part of the sodium carboxylates on the PAM molecular chain are converted into carboxyl groups. Under the combined action of catalysts I and II, the carboxyl groups of PAA or PMAA generate carboxyl free radicals and methylene free radicals. The coupling termination reaction between the carboxyl free radicals and methylene free radicals in the molecules generates covalent bonds, cross-linking the PAA or PAM molecules to obtain a high-viscosity cross-linked gel structure.

[0033] (3) When (meth)acrylic acid monomer molecules are used as crosslinking agents, the highly active double bonds in the monomer molecules are initiated to undergo free radical polymerization under the action of catalysts I and II, and are converted into PAA, PMAA or PAA-co-PMAA polymers. The hydrogen and sodium of (meth)acrylic acid monomers, PAA, PMAA, etc. are exchanged, and the free radical polymerization of active (meth)acrylic acid monomers and the crosslinking reaction between molecular chains occur simultaneously. This simultaneous reaction feature improves the overall reaction efficiency, facilitates the regulation of the crosslinking reaction process, and adjusts the viscosity of the thickener (the time it takes for the fracturing fluid to take effect).

[0034]

[0035] (4) As shown in VI, during the cross-linking reaction of the PAM molecular chain, it is not necessary to adjust the pH value of the aqueous solution. Compared with the traditional high-priced zirconium, chromium, and aluminum ion cross-linking agents, the present invention not only reduces unnecessary acid and alkali consumption, but also simplifies the fracturing construction process, which is beneficial to environmental protection.

[0036] (5) Silver ions are used as catalyst I. Compared with toxic high-valent zirconium, chromium, and aluminum ions, silver ions have stronger bactericidal and algae-inhibiting properties, and can effectively inhibit the reproduction and corrosion of various bacteria or algae in the environment, effectively extending the service life of drilling equipment.

[0037] (6) Due to the high efficiency of the system reaction, the cross-linking degree of PAM and P(M)AA can be adjusted by adjusting the feed amount of the oxidant component (catalyst II), so that the viscosity-forming time of the thickener (the time it takes for the fracturing fluid to take effect) can be flexibly adjusted according to process requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 .The apparent viscosity of the flowback aqueous solution (1%) of Example 1 and Comparative Example 1 at different dissolution times.

[0039] Figure 2 .Relationship curve between different solution concentrations (after stirring for 10 minutes) and viscosity of Example 1 and Comparative Example 1.

[0040] Figure 3 .Thermostatic performance test of the aqueous solutions of Example 1 and Comparative Example 1 (after stirring for 10 minutes).

[0041] Figure 4 .The apparent viscosity of the flowback aqueous solution (1%) of Example 2 and Comparative Example 2 at different dissolution times.

[0042] Figure 5 .Relationship curve between different solution concentrations (after stirring for 10 minutes) and viscosity of Example 2 and Comparative Example 2.

[0043] Figure 6 .Thermostatic performance test of the aqueous solutions of Example 2 and Comparative Example 2 (after stirring for 10 minutes).

[0044] Figure 7 .The apparent viscosity of the flowback aqueous solution (1%) of Example 4 and Comparative Example 3 at different dissolution times. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] The external cross-linking heat-resistant and salt-resistant thickener has the following preparation steps:

[0048] (1) 40 parts of No. 3 white oil and 2 parts of organic bentonite were added to a reaction kettle in sequence. Under stirring (speed 117 rpm) and 90°C, 50 parts of PAM powder (I) (average particle diameter 80 μm, average molecular weight 2.8×10 7g / mol) was dispersed in No. 3 white oil. After continuing to stir for 30 minutes, the mixed solution was cooled to room temperature to obtain a basic thickener;

[0049] (2) Add 3 parts of acrylic acid monomer under stirring (117 rpm) at room temperature and stir until the mixture is uniformly mixed;

[0050] (3) In another enameled reactor, add 90 parts of deionized water and 10 parts of silver nitrate. Stir for 30 minutes at room temperature, filter, and obtain a silver nitrate solution with a mass content of 10% (store in the dark). When used as catalyst I, the added amount is 1% of the mass of the acrylic acid monomer;

[0051] (4) In another reaction kettle, add 90 parts of deionized water, 5 parts of potassium persulfate, 4 parts of ammonium persulfate, and 1 part of cerium nitrate hexahydrate, stir (at a speed of 117 rpm) for 30 minutes at room temperature, and filter to obtain a 10% aqueous solution. When used as an external catalyst II, the added amount is 5% of the mass of the acrylic acid monomer.

[0052] (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

[0053] Comparative Example 1:

[0054] 40 parts of No. 3 white oil and 2 parts of organic bentonite were added to the reaction kettle in sequence. Under stirring (speed 117 rpm) and 90°C, 50 parts of PAM powder (I) (average particle diameter 80 μm, average molecular weight 2.8×10 7 g / mol) was dispersed in No. 3 white oil. After stirring for 30 minutes, the mixed solution was cooled to room temperature to obtain a thickening liquid without adding a crosslinking agent, namely, a basic thickening agent.

[0055] a) Relationship between crosslinking time and apparent viscosity of thickener

[0056] 5.00 g of the products of Example 1 and Comparative Example 1 were weighed and added to 495.00 g of return water, respectively. The stirring blade speed was 270 rpm. The apparent viscosity of the solution at different stirring times was tested using a six-speed viscometer (rotor speed was 100 rpm). The corresponding test results are shown in FIG. Figure 1 shown.

[0057] Depend on Figure 1It can be seen that the viscosity of the backflow aqueous solution of Example 1 slowly increased from 9 minutes, and after 10 minutes of stirring, the viscosity increased rapidly. This indicates that during the stirring process, a cross-linking reaction occurred between the molecular chains. After 12 minutes, the cross-linking reaction tended to be moderate, and the viscosity of the solution reached a high value of about 85 mPa·s. The viscosity of Comparative Example 1 did not change much (slightly fluctuated) during the entire dissolution process. Within 6-8 minutes, the basic thickener was basically dissolved, and the effect on the viscosity was not obvious if the stirring time was extended.

[0058] It shows that the external cross-linking thickener of the present invention has a viscosity far superior to that of the basic thickener and good salt resistance, and meets the high viscosity requirements of continuous preparation of fracturing operations. In addition, under the joint action of catalysts I and II, free radical polymerization of acrylic acid and cross-linking reaction of PAA and PAM molecules occur.

[0059] b) Effect of thickener dosage on the viscosity of its aqueous solution

[0060] Different masses of Example 1, catalyst and Comparative Example 1 were weighed and added to corresponding masses of return water and seawater, respectively. The apparent viscosity of the solution was measured by stirring and dissolving for 10 minutes using a six-speed viscometer (rotor speed was 100 rpm). The corresponding test results are shown in FIG. Figure 2 shown.

[0061] Depend on Figure 2 The test results show that under the same dissolution conditions, the viscosity of the aqueous solution of Example 1 with the catalyst is higher than that of the aqueous solution of Comparative Example 1, and the viscosity increases with the increase of the amount of thickener. Figure 1 and Figure 2 It can be seen from the test results that the thickener of the present invention can initiate free radical polymerization and chemical cross-linking reaction of PAM molecular chains at room temperature without additional adjustment of the pH value of water.

[0062] It shows that the thickener solution after chemical crosslinking has good salt resistance. That is, the external crosslinking thickener of the present invention has excellent viscosity and salt resistance, and as the amount of thickener increases, the viscosity also increases.

[0063] c) Temperature resistance of thickener solution

[0064] The products of Example 1 and Comparative Example 1 were prepared into a thickener solution with a mass fraction of 1.0% using seawater. -1 Under the conditions, the temperature rises from 60℃ to 200℃, and the viscosity of the thickener solution under different temperature conditions is measured. The results are as follows Figure 3 shown.

[0065] from Figure 3It can be seen that in Example 1 with an external crosslinking agent, the viscosity of the thickener solution does not change much within the temperature range of the experimental test, and maintains a relatively high viscosity value. Relatively speaking, as the ambient temperature increases, the viscosity of the seawater solution of Comparative Example 1 decreases rapidly, indicating that the temperature resistance of the non-crosslinked thickener solution is poor.

[0066] This indicates that the external cross-linking thickener of the present invention is less affected by temperature and has excellent temperature resistance. This indicates that after chemical cross-linking, the viscosity of the obtained thickener gel is less sensitive to ambient temperature and the solution has good temperature resistance.

[0067] Example 2

[0068] The external cross-linking heat-resistant and salt-resistant thickener has the following preparation steps:

[0069] (1) Add 35 parts of No. 5 white oil and 15 parts of No. 32 white oil to a reactor, add 5 parts of organic bentonite under stirring (rotation speed of 117 rpm) and room temperature, and stir for 30 minutes. Then add 50 parts of polymer (II) powder (average particle diameter 120 μm, average molecular weight 1.5×10 7 g / mol) were mixed together, the speed was controlled to be 117 rpm, and the stirring time was 30 min to obtain a basic thickener;

[0070] (2) Add 0.5 parts of PAA (average molecular weight 500 g / mol) crosslinker under stirring and stir for 30 min;

[0071] (3) In another reaction kettle, add 99 parts of deionized water and 1 part of silver nitrate. Stir at room temperature for 30 minutes, filter, and obtain a silver nitrate solution with a mass percentage of 1% (store in the dark). When used as an external catalyst I, the added amount is 5% of the mass of the acrylic acid monomer;

[0072] (4) In another reaction kettle, add 95 parts of deionized water, 3 parts of sodium persulfate, 1 part of ammonium persulfate, and 1 part of potassium hydrogen persulfate, stir (at a speed of 117 rpm) for 30 minutes at room temperature, and filter to obtain a 5% by mass aqueous solution. When used as an external catalyst II, the added amount is 2% of the mass of the acrylic acid monomer.

[0073] (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

[0074] Comparative Example 2:

[0075] (1) Add 35 parts of No. 5 white oil and 15 parts of No. 32 white oil to a reactor, add 5 parts of organic bentonite under stirring (rotation speed of 117 rpm) and room temperature, and stir for 30 minutes. Then add 50 parts of polymer (II) powder (average particle diameter 120 μm, average molecular weight 1.5×10 7 g / mol) were mixed together, the rotation speed was controlled to be 117 rpm, and the stirring time was 30 min; and filtering was performed to obtain a thickener without adding a cross-linking agent.

[0076] a) Relationship between crosslinking time and apparent viscosity of thickener

[0077] 5.00 g of the products of Example 2 and Comparative Example 2 were weighed and added to 495.00 g of seawater, respectively. The stirring speed of the stirring blade was 270 rpm. The apparent viscosity of the solution at different stirring times was tested using a six-speed viscometer (rotor speed was 100 rpm). The corresponding test results are shown in FIG. Figure 4 shown.

[0078] Depend on Figure 4 It can be seen that the viscosity of the backflow solution of Example 2 began to rise slowly after 7 minutes of stirring, and the viscosity rose rapidly after 9 minutes. This indicates that during the stirring process, a cross-linking reaction occurred between the PAM molecular chains, and the cross-linking reaction tended to be moderate after 11 minutes, and the viscosity of the solution reached a relatively stable value of about 87 mPa·s. The viscosity of Comparative Example 2 did not change much during the entire dissolution process, indicating that Comparative Example 2 was basically dissolved in the backflow water within 5 minutes, and further extending the stirring time did not significantly affect the viscosity of the solution of Comparative Example 2.

[0079] It shows that the external cross-linking thickener of the present invention has a viscosity far superior to that of the basic thickener and good salt resistance, and meets the high viscosity requirements of continuous preparation of fracturing operations. It shows that under the joint action of catalysts I and II, a cross-linking reaction of PAA and PAM molecules occurs.

[0080] b) Effect of thickener dosage on the viscosity of its aqueous solution

[0081] Different masses of Example 1, catalyst and Comparative Example 1 were weighed and added to the corresponding return water and seawater, respectively. The apparent viscosity of the solution was measured by stirring and dissolving for 10 min using a six-speed viscometer (rotor speed was 100 rpm). The corresponding test results are shown in FIG. Figure 5 shown.

[0082] Depend on Figure 5 The viscosity test results show that under the same conditions, the viscosity of the return water or seawater solution of Example 2 / catalyst is higher than that of the aqueous solution of Comparative Example 2, and the viscosity increases with the increase of the amount of thickener. Figure 4 and Figure 5It can be seen from the test results that the present invention can trigger the chemical cross-linking reaction of PAA and PAM molecular chains at room temperature without additional adjustment of the pH value of water, and the thickener solution after chemical cross-linking has good salt resistance and stability.

[0083] It shows that under the joint action of catalysts I and II, the molecular chains of polymer PAA or PAM are covalently cross-linked, which significantly improves the apparent viscosity of its aqueous solution and exhibits good salt resistance (resistance to calcium and magnesium ions). Moreover, as the amount of thickener increases, the viscosity also increases.

[0084] c) Temperature resistance of thickener solution

[0085] The products of Example 2 and Comparative Example 2 were prepared into a thickener solution with a mass fraction of 1.0% using seawater and subjected to a rheometer with a shear rate of 170 s -1 Under the conditions, the temperature rises from 60℃ to 200℃, and the viscosity of the thickener solution under different temperature conditions is measured. The results are as follows Figure 6 shown.

[0086] from Figure 6 It can be seen that in Example 2 with an external crosslinking agent, the viscosity of the thickener solution changes less within the measured temperature range and always maintains a high viscosity value. This indicates that after chemical crosslinking, the viscosity of the obtained thickener gel is less sensitive to temperature and the solution has better temperature resistance. Relatively speaking, as the ambient temperature increases, the viscosity of the seawater solution of Comparative Example 2 decreases faster, indicating that the uncrosslinked thickener solution has poor temperature resistance. In addition, from Figure 6 It can be seen that at the same solution concentration (1.0%), the viscosity of the thickener solution at 60°C is nearly 10 mPa·s higher than that at room temperature, indicating that at higher temperatures, catalysts I and II have better catalytic effects on the cross-linking reaction of polymer molecular chains, and higher ambient temperatures are conducive to improving the conversion efficiency of the cross-linking reaction.

[0087] It shows that the external cross-linking thickener of the present invention is less affected by temperature in seawater and has excellent temperature resistance. It shows that after chemical cross-linking, the viscosity of the obtained thickener gel is less sensitive to ambient temperature and the solution has good temperature and salt resistance.

[0088] Example 3

[0089] The external cross-linking heat-resistant and salt-resistant thickener has the following preparation steps:

[0090] (1) 45 parts of No. 7 white oil were added to a reaction kettle, and 3.5 parts of organic bentonite were added under stirring (rotation speed of 117 rpm) and room temperature, and stirred for 30 minutes. Then 60 parts of polymer (III) powder (average particle diameter of 110 μm, average molecular weight of 2.1×10 7g / mol) were mixed together, the speed was controlled to be 117 rpm, and the stirring time was 30 min to obtain a basic thickener;

[0091] (2) Add 2 parts of PEO-b-PAA (where the average molecular weight of the PAA block is 8200 g / mol) crosslinker under stirring, control the speed to 117 rpm, and stir for 30 min;

[0092] (3) In another reaction kettle, add 97 parts of deionized water and 3 parts of silver nitrate. Stir at room temperature for 30 minutes, filter, and obtain a 3% silver nitrate solution (store in dark). When used as an external catalyst I, the added amount is 1% of the mass of PEO-b-PAA;

[0093] (4) In another reaction kettle, add 99 parts of deionized water and 1 part of potassium persulfate, stir (rotation speed is 117 rpm) for 30 minutes at room temperature, and filter to obtain a 1% aqueous solution. When used as an external catalyst II, the addition amount is 5% of the mass of PEO-b-PAA.

[0094] (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

[0095] The product of Example 3 was prepared into a thickener solution with a mass fraction of 1.0% using seawater. -1 Under the conditions of 120℃, the viscosity of the thickener solution is 67±2mPa.s. Under the same temperature, the viscosity of 1% seawater solution without crosslinking agent and catalyst thickener is 24±1mPa.s.

[0096] Example 4

[0097] The external cross-linking heat-resistant and salt-resistant thickener has the following preparation steps:

[0098] (1) 20 parts of No. 3 white oil and 25 parts of No. 32 white oil were added to a reaction kettle in sequence. Under the conditions of 70°C and stirring (speed 117 rpm), 3 parts of organic bentonite were added and stirred for 30 minutes. 60 parts of polymer (IV) powder (average particle diameter 85 μm, average molecular weight 1.5×10 7 g / mol) were mixed together, the rotation speed was controlled at 117 rpm, and the stirring time was 45 minutes to obtain a basic thickener;

[0099] (2) Under stirring conditions, 0.5 parts of PAA-co-PMAA (average molecular weight 500,000 g / mol) crosslinker was added, the speed was controlled at 117 rpm, and stirring was carried out for 30 min;

[0100] (3) In another reaction kettle, add 98 parts of deionized water and 2 parts of silver nitrate. Stir at room temperature for 30 minutes, filter, and obtain a 2% silver nitrate solution (store in dark). When used as an external catalyst I, the added amount is 4.5% of the mass of PEO-b-PAA;

[0101] (4) In another reaction kettle, add 90 parts of deionized water, 2 parts of potassium persulfate, 5 parts of potassium hydrogen persulfate, and 3 parts of cerium ammonium nitrate, stir (speed of 117 rpm) for 30 minutes at room temperature, and filter to obtain a 10% aqueous solution. When used as external catalyst II, the addition amount is 2.5% of the mass of PEO-b-PAA.

[0102] (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

[0103] Comparative Example 3

[0104] 20 parts of No. 3 white oil and 25 parts of No. 32 white oil were added to the reactor in sequence. 3 parts of organic bentonite were added at 70°C and stirred (speed 117 rpm) for 30 minutes. 60 parts of polymer (IV) powder (average particle diameter 85 μm, average molecular weight 1.5×10 7 g / mol) were mixed together, the speed was controlled at 117 rpm, and the stirring time was 45 minutes; and filtered to obtain a thickener without adding a crosslinking agent;

[0105] a) Apparent viscosity of thickener solution at different dissolution times

[0106] 5.00 g of the products of Example 4 and Comparative Example 3 were weighed and added to 495.00 g of seawater, respectively, with the stirring blade rotating at 270 rpm, and stirred for 2 minutes, 5 minutes and 10 minutes, respectively. Then, the apparent viscosity of the solution at different stirring times was tested using a six-speed viscometer (rotor speed was 100 rpm), and the corresponding test results are shown in Table 1.

[0107] Table 1. Apparent viscosity of two thickeners at different dissolution times

[0108]

[0109] It is shown that the external cross-linking thickener of the present invention has a viscosity far superior to that of the basic thickener and better salt resistance, and meets the high viscosity requirement of continuous preparation of fracturing operations.

[0110] b) Relationship between crosslinking time and apparent viscosity of thickener

[0111] 5.00 g of the products of Example 4 and Comparative Example 3 were weighed and added to 495.00 g of seawater, respectively. The stirring speed of the stirring blade was 270 rpm. The apparent viscosity of the solution at different stirring times was tested using a six-speed viscometer (rotor speed was 100 rpm). The corresponding test results are shown in FIG. Figure 7 shown.

[0112] Depend on Figure 7 It can be seen that the viscosity of the backflow aqueous solution of Example 4 slowly increased after stirring for 5 minutes, and the viscosity increased rapidly after 10 minutes, indicating that a cross-linking reaction occurred between molecular chains during the stirring process. The cross-linking reaction tended to be moderate after 11 minutes, and the viscosity of the solution reached a relatively stable value of about 90 mPa·s. The viscosity of Comparative Example 3 did not change much during the entire dissolution process, indicating that Comparative Example 2 was basically dissolved in seawater within 7 minutes. Continuing to extend the stirring time did not significantly affect the viscosity of the backflow aqueous solution of Comparative Example 3.

[0113] Furthermore, it should be noted that the pH value of water is not adjusted during the dissolution of the thickener. That is, the cross-linking reaction of the polymer can occur at room temperature and with the original water quality, and the cross-linking speed is related to the type of cross-linking agent, the type and amount of catalyst (I and II). The cross-linking reaction speed will be appropriately accelerated by using a larger amount of catalyst; the use of high molecular weight PAA or PMAA polymers can accelerate the cross-linking reaction of polymer molecular chains.

[0114] Example 5

[0115] The external cross-linking heat-resistant and salt-resistant thickener has the following preparation steps:

[0116] (1) 20 parts of No. 5 white oil, 10 parts of No. 7 white oil, and 15 parts of No. 15 white oil were added to a reaction kettle in sequence. At 70° C. and stirring conditions (stirring speed 117 rpm), 2.5 parts of organic bentonite were added and stirred for 30 minutes. 60 parts of polymer (V) powder (average particle diameter 110 μm, average molecular weight 2.4×10 7 g / mol), the speed was controlled at 117 rpm, and after stirring for 60 minutes, the mixture was cooled to room temperature to obtain a basic thickener;

[0117] (2) Add cross-linking agent: 0.5 parts of AA, 0.5 parts of PMAA (average molecular weight of 500 g / mol), 1 part of PEO-b-PMAA (average molecular weight of PMAA block is 12000 g / mol), 1 part of PEO-b-PAA-co-PMAA (molecular weight of PAA-co-PMAA segment is 500000 g / mol), and stir at room temperature (speed of 117 rpm) for 30 min;

[0118] (3) In another reaction kettle, add 92 parts of deionized water and 8 parts of silver nitrate. Stir at room temperature for 30 minutes, filter, and obtain a silver nitrate solution with a mass percentage of 8% (store in the dark). When used as an external catalyst I, the added amount is 3.5% of the mass of the crosslinking agent;

[0119] (4) In another reaction kettle, add 90 parts of deionized water, 1 part of potassium hydrogen persulfate, 3 parts of potassium persulfate, 3 parts of sodium persulfate, 2 parts of cerium nitrate hexahydrate, and 1 part of cerium ammonium nitrate, stir (speed of 117 rpm) for 30 minutes at room temperature, and filter to obtain a 10% aqueous solution. When used as an external catalyst II, the added amount is 2% of the mass of the crosslinking agent.

[0120] (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

[0121] Comparative Example 4

[0122] 20 parts of No. 5 white oil, 10 parts of No. 7 white oil, and 15 parts of No. 15 white oil were added to the reaction kettle in sequence. Under stirring conditions (stirring speed of 117 rpm) at 70°C, 2.5 parts of organic bentonite were added and stirred for 30 minutes. 60 parts of polymer (V) powder (average particle diameter 110 μm, average molecular weight 2.4

[0123] ×10 7 g / mol), the rotation speed was controlled at 117 rpm, and after stirring for 60 minutes, the mixture was cooled to room temperature; and filtered to obtain a thickener without adding a cross-linking agent.

[0124] a) Apparent viscosity of thickener solution at different dissolution times

[0125] 5.00 g of the products of Example 5 and Comparative Example 4 were weighed and added to 495.00 g of seawater, respectively, with the stirring blade rotating at 270 rpm, and stirred for 2 minutes, 5 minutes and 10 minutes, respectively. Then, the apparent viscosity of the solution at different stirring times was tested using a six-speed viscometer (rotor speed was 100 rpm), and the corresponding test results are shown in Table 2.

[0126] It can be concluded from the data in Table 2 that the viscosity of the solution of Example 5 increases continuously with the extension of the stirring time. For example, the apparent viscosity at 10 minutes is about 1.5 times the apparent viscosity of the solution at 5 minutes. However, the apparent viscosity of Comparative Example 4 at 10 minutes is roughly equivalent to the apparent viscosity of the solution at 5 minutes. This shows that the polymer in Example 5 is continuously undergoing a cross-linking reaction during the dissolution of the polymer molecules as time goes by. In addition, the cross-linking reaction of the present invention is different from the cross-linking reaction of traditional high-valent ions such as zirconium, chromium, and aluminum, and does not require additional adjustment of the pH value of the solution.

[0127] Table 2. Apparent viscosity of two thickeners at different dissolution times

[0128]

[0129] Example 6

[0130] The external cross-linking heat-resistant and salt-resistant thickener has the following preparation steps:

[0131] (1) In a reaction kettle, 15 parts of No. 3 white oil, 10 parts of No. 5 white oil, 10 parts of No. 7 white oil, 5 parts of No. 10 white oil, 5 parts of No. 15 white oil, and 5 parts of No. 32 white oil were added in sequence, and 5 parts of organic bentonite were added. The mixture was stirred at 60° C. (speed was 117 rpm) for 30 minutes. 20 parts of polymer (I) powder (average particle diameter 80 μm, average molecular weight 2.8×10 7 g / mol), 35 parts of polymer (V) powder (average particle diameter 110 μm, average molecular weight 2.4×10 7 g / mol) were mixed together, and the stirring time was 50 minutes at 60°C with the rotation speed controlled at 117 rpm. Then, the mixed solution was cooled to room temperature to obtain a basic thickener;

[0132] (2) adding cross-linking agent: MAA 0.5 parts, PAA (average molecular weight of 1700 g / mol) 0.5 parts, PEO-b-PAA-b-PMAA (wherein the average molecular weight of the PAA-b-PMAA block is 13500 g / mol) 1 part, PEO-b-PAA-co-PMAA (wherein the molecular weight of the PAA-co-PMAA segment is 35000 g / mol) 1 part, stirring at room temperature (speed of 117 rpm) for 30 min;

[0133] (3) In another reaction kettle, add 95 parts of deionized water and 5 parts of silver nitrate. Stir at room temperature for 30 minutes, filter, and obtain a 5% by weight silver nitrate solution (store in dark). When used as an external catalyst I, the added amount is 4.2% of the crosslinking agent weight;

[0134] (4) In another reaction kettle, add 92 parts of deionized water, 4 parts of ammonium persulfate, 1 part of potassium persulfate, 1 part of sodium persulfate, 1 part of cerium nitrate, and 1 part of ammonium cerium nitrate, stir (speed of 117 rpm) for 30 minutes at room temperature, and filter to obtain an aqueous solution with a mass percentage of 8%. When used as an external catalyst II, the added amount is 3.5% of the mass of the crosslinking agent.

[0135] (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

[0136] The product of Example 6 was prepared into a thickener solution with a mass fraction of 1.0% using return water. -1 Under the conditions of 120℃, the viscosity of the thickener solution is 70±5mPa.s. Under the same temperature, the viscosity of 1% seawater solution without crosslinking agent and catalyst thickener is 25±2mPa.s.

[0137] Example 7

[0138] The external cross-linking heat-resistant and salt-resistant thickener has the following preparation steps:

[0139] (1) 30 parts of No. 3 white oil, 10 parts of No. 10 white oil, and 10 parts of No. 32 white oil were added to a reaction kettle in sequence. Under the conditions of 50° C. and stirring (stirring speed 117 rpm), 2 parts of organic bentonite were added; 30 parts of polymer (II) powder (average particle diameter 120 μm, average molecular weight 1.5×10 7 g / mol), 30 parts of polymer (III) powder (average particle diameter 110 μm, average molecular weight 2.1×10 7 g / mol) were mixed together, stirred at 50°C for 40 minutes, and then the mixed solution was cooled to room temperature to obtain a basic thickener;

[0140] (2) adding cross-linking agent: 0.5 parts of PAA (average molecular weight of 1700 g / mol), 0.5 parts of PEO-b-PMAA (average molecular weight of PMAA block of 6500 g / mol), 1 part of PEO-b-PAA-b-PMAA (average molecular weight of PAA-b-PMAA block of 13500 g / mol), 0.5 parts of PEO-b-PAA-co-PMAA (molecular weight of PAA-co-PMAA segment of 35000 g / mol), stirring at room temperature (speed of 117 rpm) for 30 min;

[0141] (3) In another reaction kettle, add 93 parts of deionized water and 7 parts of silver nitrate. Stir at room temperature for 30 minutes, filter, and obtain a silver nitrate solution with a mass percentage of 7% (store in the dark). When used as an external catalyst I, the added amount is 4% of the mass of the crosslinking agent;

[0142] (4) In another reaction kettle, add 93 parts of deionized water, 2 parts of ammonium persulfate, 1 part of potassium hydrogen persulfate, 1 part of potassium persulfate, 1 part of sodium persulfate, 1 part of cerium nitrate, and 1 part of ammonium cerium nitrate, stir (speed of 117 rpm) for 30 minutes at room temperature, and filter to obtain a 7% aqueous solution. When used as an external catalyst II, the added amount is 4% of the mass of the crosslinking agent.

[0143] (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

[0144] The product of Example 7 was prepared into a thickener solution with a mass fraction of 1.0% using return water. -1 Under the conditions, the viscosity of the thickener solution was 63±4mPa.s at 120°C. At the same temperature, the viscosity of a 1% seawater solution without crosslinking agent and catalyst thickener was 23±2mPa.s.

[0145] Example 8

[0146] The external cross-linking heat-resistant and salt-resistant thickener has the following preparation steps:

[0147] (1) 20 parts of No. 3 white oil, 10 parts of No. 5 white oil, 15 parts of No. 15 white oil, and 5 parts of No. 32 white oil were added to a reaction kettle in sequence. Under the conditions of 65° C. and stirring (stirring speed 117 rpm), 2.5 parts of organic bentonite were added; 20 parts of polymer (II) powder (average particle diameter 120 μm, average molecular weight 1.5×10 7 g / mol), 10 parts of polymer (III) powder (average particle diameter 110 μm, average molecular weight 2.1×10 7 g / mol), 25 parts of polymer (V) powder (average particle diameter 110 μm, average molecular weight 2.4×10 7 g / mol) were mixed together, stirred at 65°C for 30 minutes, and then the mixed solution was cooled to room temperature to obtain a basic thickener;

[0148] (2) adding cross-linking agent: 0.5 parts of PMAA (average molecular weight of 500 g / mol), 0.5 parts of PEO-b-PAA (average molecular weight of PAA block of 8200 g / mol), 0.5 parts of PEO-b-PAA-b-PMAA (average molecular weight of PAA-b-PMAA block of 13500 g / mol), 0.5 parts of PEO-b-PAA-co-PMAA (molecular weight of PAA-co-PMAA segment of 35000 g / mol), and stirring at room temperature (speed of 117 rpm) for 45 min;

[0149] (3) In another reaction kettle, add 95 parts of deionized water and 5 parts of silver nitrate. Stir at room temperature for 30 minutes, filter, and obtain a 5% by weight silver nitrate solution (store in dark). When used as an external catalyst I, the added amount is 5% of the crosslinking agent weight;

[0150] (4) In another reaction kettle, add 93 parts of deionized water, 3 parts of ammonium persulfate, 2 parts of potassium persulfate, 1 part of cerium nitrate, and 1 part of cerium nitrate hexahydrate, stir (at a speed of 117 rpm) for 30 minutes at room temperature, and filter to obtain a 7% aqueous solution. When used as an external catalyst II, the added amount is 4% of the mass of the crosslinking agent.

[0151] (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

[0152] Comparative Example 5

[0153] 20 parts of No. 3 white oil, 10 parts of No. 5 white oil, 15 parts of No. 15 white oil, and 5 parts of No. 32 white oil were added to the reactor in sequence. Under the conditions of 65°C and stirring (stirring speed 117 rpm), 2.5 parts of organic bentonite were added; 20 parts of polymer (II) powder (average particle diameter 120 μm, average molecular weight 1.5×10 7 g / mol), 10 parts of polymer (III) powder (average particle diameter 110 μm, average molecular weight 2.1×10 7 g / mol), 25 parts of polymer (V) powder (average particle diameter 110 μm, average molecular weight 2.4×10 7 g / mol) were mixed together, stirred at 65° C. for 30 minutes, and then the mixed solution was cooled to room temperature; filtered to obtain a thickener without adding a cross-linking agent.

[0154] Performance tests of Example 8 and Comparative Example 5:

[0155] 5.00 g of the products of Example 8 and Comparative Example 5 were weighed and added to 495.00 g of seawater, respectively, with the stirring blade rotating at 270 rpm, and stirred for 2 minutes, 5 minutes and 10 minutes, respectively. Then, the apparent viscosity of the solution at different stirring times was tested using a six-speed viscometer (rotor speed was 100 rpm), and the corresponding test results are shown in Table 3.

[0156] Table 3. Apparent viscosity of two thickeners at different dissolution times

[0157]

[0158]

[0159] It can be concluded from the data in Table 3 that the viscosity of the solution of Example 8 increases continuously with the extension of the stirring time. For example, the apparent viscosity at 10 minutes is about 1.4 times the apparent viscosity of the solution at 5 minutes. However, the apparent viscosity of Comparative Example 5 at 10 minutes is roughly equivalent to the apparent viscosity of the solution at 5 minutes. This shows that the polymer in Example 8 continues to undergo a cross-linking reaction while the polymer dissolves as the stirring time increases. In addition, the cross-linking reaction of the present invention does not require adjustment of the pH value of the solution.

[0160] It should be noted that the cross-linking reaction rate (ie, tackification time) of the thickener of the present invention is adjustable.

[0161] Table 4 shows the viscosity-initiating time and apparent viscosity (measured after stirring for 10 minutes) of the backflow aqueous solutions of Examples 1-8 under the action of different cross-linking agents and catalysts.

[0162] Table 4. Viscosity onset time and apparent viscosity of the backflow aqueous solution of Examples 1-8 under the action of different crosslinking agents and catalysts

[0163]

[0164]

[0165] As shown in Table 4, the present invention can conveniently adjust the viscosity time of the thickener within a time range of 6-12 minutes or even wider by adjusting the type and amount of the cross-linking agent and the catalyst. The cross-linking time of traditional cross-linking agents such as zirconium ions is only 2-3 minutes. Since the cross-linking time is too short, sometimes the thickener solution does not enter the fine cracks of the rock layer, and the viscosity of the thickener solution becomes very large, affecting the effect of the fracturing fluid. The thickener of the present invention uses poly (methyl) acrylic acid or poly (methyl) acrylic acid block polymer as a cross-linking agent, and uses silver nitrate and peroxide as a catalyst, which can conveniently adjust the cross-linking time of the polymer molecular chain within a wider time range, so that the thickener can easily penetrate into small rock cracks at a lower viscosity, and then cross-link to obtain high viscosity, which can carry more sand particles, effectively implement supercharging, and optimize the construction process.

[0166] The present invention solves the problem that the traditional high-valent ion cross-linking agent needs to adjust the pH value of the aqueous solution, and the toxic side effects of high-valent ions polluting the environment by adding non-toxic acrylic acid or polyacrylic acid as a cross-linking agent, and using a trace amount of silver nitrate in combination with persulfate, cerium nitrate, etc. as a catalyst. The silver nitrate-persulfate redox composite catalyst of the present invention promotes the cross-linking of polyacrylic acid and PAM molecular chains, improves the viscosity of the thickener solution, solves the defect of poor heat and salt resistance of traditional thickeners, and can meet the requirements of continuous fracturing operations. Finally, the cross-linking reaction rate (i.e., the viscosity time) of the thickener of the present invention can be flexibly adjusted.

[0167] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of equivalent transformations, and these equivalent transformations all belong to the protection scope of the present invention. It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. Externally cross-linked heat-resistant and salt-resistant thickener, characterized in that The thickener comprises, by weight: Wherein, the basic thickener comprises, by weight: Anionic polyacrylamide (PAM) 50-60 parts, 40-50 parts of white oil, 2-5 parts of thixotropic additive, The catalyst I is silver nitrate; The catalyst II is at least one of ammonium persulfate, potassium persulfate, sodium persulfate, potassium hydrogen persulfate, ammonium cerium nitrate, cerium nitrate, and cerium nitrate hexahydrate; The anionic polyacrylamide (PAM) is selected from one or more of polymers (I) to (V), Among them, the average diameter of anionic polyacrylamide (PAM) is 80-120 μm, and the molecular weight is 1.5×10 7 g / mol-2.8×10 7 g / mol, a, o, m, n, p are all positive integers ≥ 1, m:n = 1.5 to 3:1; The cross-linking agent is at least one of acrylic acid (AA), methacrylic acid (MAA), polyacrylic acid (PAA), polymethacrylic acid (PMAA), copolymer of acrylic acid and methacrylic acid (PAA-co-PMAA), polyethylene glycol-b-polyacrylic acid (PEO-b-PAA), polyethylene glycol-b-polymethacrylic acid (PEO-b-PMAA), polyethylene glycol-b-polyacrylic acid-b-polymethacrylic acid (PEO-b-PAA-b-PMAA), and polyethylene glycol-b-polyacrylic acid copolymerized with methacrylic acid (PEO-b-PAA-co-PMAA); and the thickener is prepared according to the following method: (1) white oil and thixotropic additive are uniformly mixed, anionic polyacrylamide (PAM) is dispersed in the white oil under stirring conditions from room temperature to 90° C., and then cooled to room temperature to obtain a basic thickener; (2) Add a crosslinking agent under stirring conditions at room temperature and stir until the mixture is uniform; (3) In another container, add deionized water and prepare a 1%-10% (mass percentage) solution of catalyst I under light-proof conditions; (4) In another container, add deionized water to prepare a 1%-10% (mass percentage) solution of Catalyst II; (5) Adding catalyst I and catalyst II into step (3) to obtain a thickening agent.

2. The thickener according to claim 1, characterized in that The number average molecular weight of the P(M)AA block in the PAA, PMAA or PEO-bP(M)AA, PEO-b-PAA-co-PMAA block polymer is in the range of 500-500000 g / mol.

3. The thickener according to claim 1, characterized in that The thixotropic additive is organic bentonite.